1983
DOI: 10.1523/jneurosci.03-12-02463.1983
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of 3H-amino acids into proteins in a partially purified fraction of axoplasm: evidence for transfer RNA-mediated, post- translational protein modification in squid giant axons

Abstract: Transfer RNA (tRNA) has been demonstrated to be present in axons of both invertebrates and the higher vertebrates, but nothing is known of its role in the metabolism of the axon. The present experiments were performed to determine whether tRNA functions in axons as a participant in post-translational protein modification of endogenous proteins. RNA was extracted from the axoplasm of squid giant axons and incubated with a variety of 3H-amino acids, aminoacyl-tRNA synthetases (obtained from squid optic lobe), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…The second argument is that many components of translation machinery are found in axons, including in squid giant axoplasm, and therefore this serves as prima facie evidence that translation must be occurring in this cellular compartment (Alvarez et al 2000;Giuditta et al 2008). These data include reports of abundant tRNAs (Black and Lasek 1977;Ingoglia et al 1983), mRNAs (Capano et al 1987;Gioio et al 1994;Kaplan et al 1992;Rapallino et al 1988), various elongation and initiation factors (Giuditta et al 1980;Giuditta et al 1986;Giuditta et al 1991;Kar et al 2013), rRNA (Giuditta et al 1980;Perrone-Capano et al 1999), and even polyribosomes that can be translated in vitro to produce various proteins (Giuditta et al 1991;Sotelo et al 1999). Given this apparent translation capacity of squid axoplasm it should then be possible for isolated axoplasm to synthesize proteins directly from radioactive amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The second argument is that many components of translation machinery are found in axons, including in squid giant axoplasm, and therefore this serves as prima facie evidence that translation must be occurring in this cellular compartment (Alvarez et al 2000;Giuditta et al 2008). These data include reports of abundant tRNAs (Black and Lasek 1977;Ingoglia et al 1983), mRNAs (Capano et al 1987;Gioio et al 1994;Kaplan et al 1992;Rapallino et al 1988), various elongation and initiation factors (Giuditta et al 1980;Giuditta et al 1986;Giuditta et al 1991;Kar et al 2013), rRNA (Giuditta et al 1980;Perrone-Capano et al 1999), and even polyribosomes that can be translated in vitro to produce various proteins (Giuditta et al 1991;Sotelo et al 1999). Given this apparent translation capacity of squid axoplasm it should then be possible for isolated axoplasm to synthesize proteins directly from radioactive amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent lack of other cytoplasmic RNAs, notably rRNAs, confirmed that axons could not synthesize proteins and suggested that axoplasmic tRNA comprised only a few species serving a different function such as addition of activated amino acids to the native proteins (161). These data were contradicted by two independent observations.…”
Section: The Squid Giant Axonmentioning
confidence: 94%
“…First, selective assays of single tRNAs and aminoacyltRNA synthetases demonstrated that the giant axon contained as many as six different tRNAs and the corresponding synthetases. In other words, all the tRNA species assayed for were in the axoplasm (161). As these components could not be involved in other activities but translation processes, the findings contributed to tilt the balance in favor of axonal protein synthesis.…”
Section: The Squid Giant Axonmentioning
confidence: 95%
“…identifi ed as ribosomal, messenger and transfer (Edström et al, 1962;Black and Lasek, 1977;Koenig, 1979;Ingoglia et al, 1983;Jirikowski et al, 1990;Mohr and Richter, 1992;Wensley et al, 1995). Notwithstanding, the role of axoplasmic RNAs has been controversial as it was deemed unrelated to local protein synthesis (Black and Lasek, 1977;Ingoglia et al, 1983;Jirikowski et al, 1990;Mohr and Richter, 1992;Wensley et al, 1995) since the notion that axons do not synthesize proteins prevailed.…”
Section: Scrutiny Of Inability Of Axons To Synthesize Proteinsmentioning
confidence: 99%
“…Notwithstanding, the role of axoplasmic RNAs has been controversial as it was deemed unrelated to local protein synthesis (Black and Lasek, 1977;Ingoglia et al, 1983;Jirikowski et al, 1990;Mohr and Richter, 1992;Wensley et al, 1995) since the notion that axons do not synthesize proteins prevailed. If we track this deeply rooted notion back to its roots, we fi nd that electron microscopists did not include ribosomes in the inventory of the axoplasm, and that cell biologists considered axons to be ribosome-free, based on this one and only datum.…”
Section: Scrutiny Of Inability Of Axons To Synthesize Proteinsmentioning
confidence: 99%